Carbon dioxide diffuse emission and thermal energy release from hydrothermal systems at Copahue–Caviahue Volcanic Complex (Argentina) - Chiodini, Giovanni (2015)
Fil: Chiodini, Giovanni. Istituto Nazionale di Geofisica e Vulcanologia, Sezione di Bologna. Bologna, Italia.